PENGARUH PENGGUNAAN ADMIXTURE TIPE E DENGAN PENGURANGAN JUMLAH KADAR AIR TERHADAP NILAI SLUMP DAN KUAT TEKAN BETON PADA QUARRY EX. CIKERUH - Juliar, Eka; Suson Rudianto, Encep (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
This study aims to determine the effect of using type E admixture by reducing the amount of water content on the slump value and compressive strength of concrete in quarry Ex. noisy. The mixture used in this study was a normal concrete mix, a mixture with the addition of Type E admixture 1%, 1.5% and 2% taken from the weight of cement, by making cylindrical test objects measuring 15 cm x 30 cm with a total sample of 12 pieces and concrete compressive strength test plan at the age of 7, 14 and 28 days. The results of this study for normal concrete mixtures obtained a slump value of 60 mm, whereas for mixtures using type E admixture, the slump value was between 62 – 67 mm. From this study, the ideal mix was produced for a mixture using 1.5% E type admixture with a compressive strength of 22.64 MPa, while for normal concrete mixtures with a compressive strength of 20.38 MPa, for a mixture using E type 1 admixture % obtained a compressive strength of 21.23 Mpa, and the mixture with the addition of 2% type E admixture obtained a compressive strength of 21.79 Mpa. However, the mixture with the addition of 2% E type admixture experienced a decrease in compressive strength compared to the previous mixture, namely with the addition of 1.5% admixture.